Relationship between university climate and self-efficacy of counseling students in selected Malaysian universities - Bagheri, Elham (2012)
Self-efficacy of counsellors has been one of the main focuses of counselling research due to the influential impact of counsellors’ perceptions towards their counselling abilities and subsequently their counselling effectiveness. Hence, developing counselling selfefficacy among university counselling students as prospective counsellors have attracted researchers' attention based on the assumption that counselling self-efficacy can be developed and improved through counsellor education and training programs. The main purpose of the study is to determine whether there is a relationship between university climate and counselling students' self-efficacy. This study employed a correlation and descriptive research design. The sample consists of one hundred and nine final year undergraduate counselling students who were undergoing their counselling programs from University Putra Malaysia (UPM),University of Malaya (UM), and Islamic Science University Malaysia (USIM) were randomly selected. The research questionnaire consists of six main sections. The first section is about demographic information; the second section consists of Counsellor Activity Self- Efficacy Scales to measure students’ counselling self-efficacy (CASES, Lent et al., 2003); the third section consist of university climate questionnaire, which contained fourteen items of university environment (University Environment, Gloria et al., 1996),nineteen items of university facilities (University Facility, Poh & Anion et al., 2006), seventeen items of friends social support (Gloria et al., 1999), and the last five items were Mentoring Scale developed by Gloria (1993) to measure supervision. The data was analyzed using the Pearson Product Moment Correlation Coefficient and the Multiple Linear Regression. The result showed that there was a significant relationship between university environment and counselling student’s self-efficacy, r =.92(p<0.05). Furthermore, there was a significant relationship between friends social support and counselling student’s self-efficacy, r = .85, p< 0.05. The finding also revealed a significant relationship between supervision and counselling student’s selfefficacy, r = .85, p<0.05. The significant relationship was found between university facilities and counselling student’s self-efficacy, r =.90, p< 0.05. The multiple linear regression analysis showed that counselling students’ self-efficacy is explained 93% by the component of university climate, R2=0.93, F(1,108) =375.68, p< 0.05. These results indicated that overall students’ self-efficacy can be predicted by the proposed multiple regression model. The findings indicate that university climate is a significant contributing factor in developing university student’s counselling self-efficacy. This is where attention should be given in order to improve the possibility of students’ success in the counselling profession. The finding also gives useful implications for counselling self-efficacy theory development, policy makers and counsellor educators.